Effectiveness of a training program for nurses' emotional management of patient death - Pais, Nelson Jacinto (2020)
Background: Death is a common reality in hospital settings, requiring nurses to adopt effective strat- egies for managing their emotions. Objectives: To assess the effectiveness of a training program for nurses' emotional management of patient death. Methodology: A one-group pretest-posttest pre-experimental study was conducted in a sample of 20 nurses working in oncology inpatient units. Data were collected using a questionnaire consisting of the Portuguese versions of the Revised Death Attitude Profile (Escala de Avaliação do Perfil de Atitudes acerca da Morte - EAPAM) and the Coping with Death Scale (ECM), and the Program Implementation Assessment Scale (EAIP), applied at three different periods. Results: The training program changed nurses' attitudes in the dimensions of fear of death and neu- tral acceptance (EAPAM). Significant differences were found in coping with one's own death and the death of others (ECM), revealing improved skills in this area. The training program was rated as very good (EAIP). Conclusion: The implementation of the training program proves to be an effective strategy for im- proving nurses' emotional management of death.